Fungi associated with datura metel L. - Aktar, Mahfuzar; Shamsi, Shamim (Dhaka University Journal of Biological Sciences, 2011)
A total of 20 species of fungi representing 12 genera were found to be associated with Datura metel L. in Bangladesh. The fungi were Alternaria alternata (Fr.) Keissler, Arthrinium saccharicola Stevenson, Aspergillus niger Van Tiegh., A. flavus Link ex Fr, Cladosporium elatum (Harz) Nannf., C. coffeanum Noack, C. gloeosporioides Penz.) Sacc., C. graminicola (Ces.) Wilson, Corynespora pruni (Berk. & Curt.) M. B. Ellis, Curvularia fallax Boedijn, C. lunata (Wakker) Boedijn, C. penniseti (Mitra) Boedijn, C. prasadii R.L. & B.L Mathur, Fusarium flocciferum Corda. Sturm's Deutschl, F. nivale (Fr.) Ces., Rabenth. Herb., Nigrospora sphaerica (Sacc.) Mason, Penicillium spp., Pseudocercospora fuligena (Roldan) Deighton, Rhizopus stolonifer (Ehrenb. ex. Fr.) Lind and one sterile unidentified fungal species. The percentage of association of Cladosporium elatum isolated from infected fruits was higher than any other fungi. Arthrinium saccharicola, Colletotrichum coffeanum, Corynespora pruni, Fusarium flocciferum and F. nivale are new records for Bangladesh. Key words: Fungi; Association; Datura metel DOI: http://dx.doi.org/10.3329/dujbs.v19i1.8947 DUJBS 2010; 19(1): 83-89